A bibliometric analysis of picture book research between 1993 and 2015. Issue 5 (4th July 2018) - Wu, Jia-Fen
Abstract : This study makes an effort to map the development of previous academic studies on picturebooks in order to provide an overview of contemporary picturebook research utilizing the HistCite (ver. 12.03.17) software. The findings are based on an analysis of 9, 763 references to 286 articles from 175 journals indexed by the Web of Science (WoS) database, from 1993 through 2015. The most prolific authors, those who are most frequently-used in title keywords, and the most frequently-cited articles are listed for purposes of examination. Results from a large-scale journal citation dataset available via HistCite provide visualization techniques which feature four major themes as determined by research interests, their size, similarity and interconnectedness.